2020
DOI: 10.1016/j.jad.2019.09.079
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of suicide in University students in England and Wales 2000/2001–2016/2017: Record linkage study

Abstract: Background: There are growing concerns about the mental health and risk of suicide amongst university students. Aim: To investigate trends in the incidence and characteristics of university student suicides in England & Wales for the academic years 2000/01 to 2016/17. Method: Record linkage between Office for National Statistics mortality data and Higher Education Statistics Agency data for England and Wales. Poisson regression and chi-squared tests were used to investigate secular trends and the characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 22 publications
2
45
0
1
Order By: Relevance
“…There was evidence of a rise in NSSH between 2000 and 2014, but this was evident in students and non-students. In keeping with national data on rates of suicide in students [10], a smaller proportion of students than non-students appear to report making suicide attempts, with no clear evidence of adverse trends over time. It is possible the rise in CMD evident in females in 2014 was linked to the rise in fees in 2012.…”
Section: Discussionsupporting
confidence: 61%
“…There was evidence of a rise in NSSH between 2000 and 2014, but this was evident in students and non-students. In keeping with national data on rates of suicide in students [10], a smaller proportion of students than non-students appear to report making suicide attempts, with no clear evidence of adverse trends over time. It is possible the rise in CMD evident in females in 2014 was linked to the rise in fees in 2012.…”
Section: Discussionsupporting
confidence: 61%
“…25 A recent study of Spanish university students reported comparable 12-month prevalence and persistence of suicidal ideation; with a mood disorder diagnosis increasing risk and a higher sense of university membership having a protective effect. 29 Peaks in student suicides have been associated with exam periods and winter months, 11 which is relevant to our study as outcome data were collected just prior to final exams in March.…”
Section: Findings In Contextmentioning
confidence: 99%
“…This age group in many countries belong to high school and university students. In England, the rate of university students’ suicide has increased since 2009 [ 2 ], and, in the USA, death by suicide was ranked second among the same age group [ 3 ]. Suicide is more prevalent in developing countries, and, according to global statistics, around 79% of the annual suicide rate belongs to developing countries [ 1 ].…”
Section: Introductionmentioning
confidence: 99%